Pengaruh Karakteristik Komite Audit dan Kualitas Audit terhadap Penyajian Kembali Laporan Keuangan - Steven Lois; Hansen Suardi; Sany Sany (Business Accounting Review, 2021)
This study's objective is to look at the impact of audit committee characteristics and thesize of the audit firm on the restatement of financial statements of financial sector companies listedon the Indonesia Stock Exchange for the period of 2016 to 2020. Measurement of audit committeecharacteristics is proxied by indicators of audit committee independence, audit committee size,number of audit committee meetings, audit committee expertise, and size of audit firm. This studyuses firm size and firm performance as control variabels. Meanwhile, the restatement of financialstatements is measured using a dummy variabel, where "1" if the company makes a restatementand "0" if not. The sample consists of 77 restatement firms and 77 control firms. There are 8 outliersamong the 77 restatement firms, therefore once the outliers are removed, the total final samplestudied is 138 observations (69 restatement firms and 69 non-restatement firms). Data wereanalyzed by logistic regression using SPSS software. According to the findings of this study, thesize of the audit committee had a negative effect on the restatement of financial statements, whilethe independence of the audit committee, the number of audit committee meetings, the expertiseof the audit committee, and the size of the audit firm did not have a negative effect on therestatement of the financial statements.